2018
DOI: 10.1186/s12958-018-0374-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the enzymatic efficiency of Liberase TM and tumor dissociation enzyme: effect on the viability of cells digested from fresh and cryopreserved human ovarian cortex

Abstract: BackgroundThe aim of this study was to examine the effectiveness of Tumor Dissociation Enzyme (TDE) on the viability of follicles after digestion of fresh and cryopreserved ovarian cortex fragments (OCFs).MethodsFresh and thawed OCF from 14 patients (29 ± 6 years), sized 20 to 210 mm3 were randomly distributed into four treatment groups and digested with 16% TDE or 0.05 mg/ml Liberase TM: Group 1, frozen OCF digested with TDE; Group 2, frozen OCF digested with LiberaseTM; Group 3, fresh OCF digested with TDE; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 81 publications
(95 reference statements)
2
10
0
Order By: Relevance
“…Weight and volume of biopsies in both group was no signi cant (p > 0.05). This was similar to a recent study by Schmidt et al It showed that the number of follicles isolated by TDE digestion is also signi cantly higher than using Liberase TM [19]. By comparison, Lierman et al presented that no statistical differences were found between Liberase TM and Liberase DH, concerning the number and type of isolated follicles [26].…”
Section: Yield Of Isolated Folliclessupporting
confidence: 88%
See 3 more Smart Citations
“…Weight and volume of biopsies in both group was no signi cant (p > 0.05). This was similar to a recent study by Schmidt et al It showed that the number of follicles isolated by TDE digestion is also signi cantly higher than using Liberase TM [19]. By comparison, Lierman et al presented that no statistical differences were found between Liberase TM and Liberase DH, concerning the number and type of isolated follicles [26].…”
Section: Yield Of Isolated Folliclessupporting
confidence: 88%
“…It is thus easy to distinguish between viable, damaged or dead cells [30]. Our study presented the percentage of bright red follicle in Group 1 digested from cryopreserved ovarian tissue was found to be signi cantly higher (p < 0.01) than Group 2 (70.9 ± 4.7% vs 63.9 ± 4.2%, respectively), similar to the observations of intense red -stained follicles in the suspension of cryopreserved ovarian tissues made by Schmidt et al (70.3 ± 6.2% in TDE vs 53.1 ± 2.0% in Liberase TM, respectively) [19].…”
Section: Quality Of Isolated Folliclessupporting
confidence: 88%
See 2 more Smart Citations
“…This may be due to the enzymes used for isolation of SSCs from testicular tissues. Generally, a variety of digestive enzymes such as trypsin, pronase, dispase, and collagenase are used, which can induce minor or major damage to cellular junctions, membranes, surface receptors, antigens, and cytosolic contents (Miersch et al 2018;Schmidt et al 2018). Therefore, Theoretically, double MACS, which is conducted sequentially using antibodies detecting different cell surface proteins, is expected to result in higher purification efficiency compared with single MACS.…”
Section: Dicussionmentioning
confidence: 99%